2016
DOI: 10.1158/0008-5472.can-15-2290
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3 Inhibition Sensitizes Acute Myeloid Leukemia Cells to 1,25D-Mediated Differentiation

Abstract: 1,25-dihydroxyvitamin D3 (1,25D), the biologically active form of vitamin D, is widely considered a promising therapy for acute myeloid leukemia (AML) based on its ability to drive differentiation of leukemic cells. However, clinical trials have been disappointing in part to dose-limiting hypercalcemia. Here we show how inhibiting glycogen synthase kinase 3 (GSK3) can improve the differentiation response of AML cells to 1,25D-mediated differentiation. GSK3 inhibition in AML cells enhanced the differentiating e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…This promotion of differentiation was greater than calcitriol alone or GSK3 inhibitors combined with an additional FDA‐approved GSK3 inhibitor in the HL‐60 cell line . When treated with GSK3 inhibitor, the majority of primary AML patient cells tested experienced a sensitization of the cells to calcitriol‐induced differentiation . In the AML cell lines, an increase in irreversible growth arrest in G 0 ‐G 1 phase of the cell cycle and decreased expression of cyclin A were observed with the GSK3 inhibitor and calcitriol treatment .…”
Section: Vitamin D Effects On Malignant Hematological Cellsmentioning
confidence: 93%
See 2 more Smart Citations
“…This promotion of differentiation was greater than calcitriol alone or GSK3 inhibitors combined with an additional FDA‐approved GSK3 inhibitor in the HL‐60 cell line . When treated with GSK3 inhibitor, the majority of primary AML patient cells tested experienced a sensitization of the cells to calcitriol‐induced differentiation . In the AML cell lines, an increase in irreversible growth arrest in G 0 ‐G 1 phase of the cell cycle and decreased expression of cyclin A were observed with the GSK3 inhibitor and calcitriol treatment .…”
Section: Vitamin D Effects On Malignant Hematological Cellsmentioning
confidence: 93%
“…In the AML cell lines, an increase in irreversible growth arrest in G 0 -G 1 phase of the cell cycle and decreased expression of cyclin A were observed with the GSK3 inhibitor and calcitriol treatment (58). The role of GSK3 in this sensitization to calcitriol-induced differentiation was confirmed by utilizing GSK3B knockdown cells, which exhibited increased differentiation and VDR transcriptional activity compared to GSK3B wild-type cells (58). GSK inhibition in combination with calcitriol led to an induction of VDR serine-208 phosphorylation, a site that affects VDR transcriptional activity, and increased JNK activation, potentially elucidating the mechanism of action of these combined treatments (58).…”
Section: Synergism With Anti-cancer Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a number of toolkit inhibitors of GSK-3β, translational studies credentialed GSK-3β as a therapeutic target in multiple tumor types including pancreatic cancer (8, 9), chronic lymphocytic leukemia (10), colon (11), renal (12) and bladder (13) cancer. More recent studies have also shown that the inhibition of GSK-3β suppressed cancer cell viability in models of glioblastoma (1416), leukemia (1720), neuroblastoma (21, 22), osteosarcoma (23), melanoma (24), ovarian (25, 26), thyroid (27), prostate (2830), breast (3133) and lung cancer (34, 35). Thus, GSK-3β has emerged as a viable therapeutic target for the treatment of a broad spectrum of different cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…After 25 minutes incubation at 37°C in the dark, cytospin slides were prepared and stained with Giemsa. Differentiated cells were recognized by their intracellular reduced dark blue formazan granules (300 cells were scored for the presence of the granules) …”
Section: Methodsmentioning
confidence: 99%